Kinetic study of the selective hydrogenation of styrene over a Pd egg-shell composite catalyst - Betti, Carolina Paola (2015)
This is a study on the kinetics of the liquid-phase hydrogenation of styrene to ethylbenzene over a catalyst of palladium supported on an inorganic–organic composite. This support has a better mechanical resistance than other commercial supports, e.g. alumina, and yields catalysts with egg-shell structure and a very thin active Pd layer. Catalytic tests were carried out in a batch reactor by varying temperature, total pressure and styrene initial concentration between 353–393 K, 10–30 bar, and 0.26–0.60 mol L−1. Kinetic models were developed on the assumptions of dissociative hydrogen chemisorption and non-negligible adsorption of hydrogen and styrene. Final chemical reaction expressions useful for reactor design were obtained. The models that best fitted the experimental data were those ones that considered the surface reaction as the limiting step. In this sense, a two-step Horiuti–Polanyi working mechanism with half hydrogenation intermediates gave the best fit of the experimental data. The heats of adsorption of styrene and ethylbenzene were also estimated.